PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL KABUPATEN DAN KOTA JAWA TIMUR TAHUN 2019-2021 - Priyono, Ibnu Anggun; Khotimah, Husnul (Universitas Trilogi, 2023)
This research aims to analyze the influence of Regional Original Income, General Allocation Funds, and Special Allocation Funds on Capital Expenditures in East Java Province. The research objects consist of 38 cities and regencies in East Java Province for the 2019 - 2021 period which can be accessed via the official website at www.djpk.kemenkeu.go.id. The data used in this research is secondary data and the sample selection method uses a saturated sampling method. The testing steps were implemented using a multiple linear regression analysis approach. The research results show that Regional Original Income has a positive effect on Capital Expenditures, General Allocation Funds have a negative effect on capital expenditures, and Special Allocation Funds have a positive effect on capital expenditures. Regional governments need to formulate budget strategies so that autonomous regions can manage them effectively, efficiently and economically.Keywords: Capital Expenditures; Special Allocation Fund; General Allocation Fund; Locally-Generated Revenue